The effects of respiratory exercises on partial pressures of gases and anxiety in the acute phase of COVID-19 infection. (18th November 2022) - Grbovic, Vesna; Markovic, Natasa; Bogojevic, Predrag; Nikolic, Jovana; Milosevic, Jelena; Simovic, Stefan; Cekerevac, Ivan; Jurišić-Škevin, Aleksandra; Zdravkovic, Nebojša; Mijailovic, Sara; Zdravkovic, Natasa
ABSTRACT: Introduction: Respiratory exercise in post-COVID-19 significantly improves pulmonary function, exercise capacity and quality of life. Our study aimed to investigate the effect of respiratory exercise on partial pressures of oxygen, carbon dioxide and oxygen saturation in arterial blood and anxiety assessed by the GAD-7 scale in the acute phase of COVID-19 infection. Methods: The study was conducted at the Clinical Center, Kragujevac, from June to July 2020. The study was a prospective clinical trial and included 62 patients with the acute-phase of COVID-19 infection (61.3% males, mean age 60.82 ± 11.72). The duration of the comprehensive pulmonary rehabilitation program was 14 days ± 2.28 days. Oxygen saturation and heart rate were determined by using the pulse oximeter, oxygen flow, and arterial blood gas analysis values by using the gas analyzer. The anxiety assessment was measured using the Generalized Anxiety Disorder (GAD-7). Results: The values of oxygen saturation significantly differed before and after the respiratory exercise sessions (95.77 vs 98.02, respectively; p < .001). After the respiratory exercise program, significantly lower values of the GAD-7 scale were observed compared to the values before the respiratory exercise program ( p = .049). A significant negative correlation was observed between oxygen saturation after respiratory exercise and age and presence of chronic obstructive pulmonary disease (ρ = −0.329; p = .013; ρ = −0.334; p = .009, respectively). GAD-7 score after respiratory exercise negatively correlated with chronic obstructive pulmonary disease and malignancy (ρ = −0.285; p = .025; ρ = −0.350; p = .005, respectively). Conclusion: The respiratory exercise program significantly improves oxygen saturation and anxiety levels in COVID-19 patients.